1999
DOI: 10.1080/10715769900301591
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis of human red blood cells induced by the combination of diethyldithiocarbamate (DDC) and divalent metals: Modulation by anaerobiosis, certain antioxidants and oxidants

Abstract: The objective of the present communication is to describe the role played by combinations between diethydithiocarbamate (DDC) and divalent metals in hemolysis of human RBC. RBC which had been treated with DDC (10-50 microM) were moderately hemolyzed (about 50%) upon the addition of subtoxic amounts of Cu2+ (50 microM). However, a much stronger and a faster hemolysis occurred either if mixtures of RBC-DDC were immediately treated either by Co2+ (50 microM) or by a premixture of Cu2+ and Co2+ (Cu:Co) (50 microM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…At present we can only speculate about the higher cytotoxicity of transition metal nanoparticles compared to the corresponding metal ions. Severe prohlems may be due to the development of free radicals or ROS, which have been shown to be released by both transition metal ions (33)(34) and (nano-)particles (5,35). In addition, it has been shown that nanoparticles together with transition metals induce ROS production which exhibits a synergistic effect of nanoparticles together with transition metals (36).…”
Section: Cytotoxicity and Oxidative Stressmentioning
confidence: 99%
“…At present we can only speculate about the higher cytotoxicity of transition metal nanoparticles compared to the corresponding metal ions. Severe prohlems may be due to the development of free radicals or ROS, which have been shown to be released by both transition metal ions (33)(34) and (nano-)particles (5,35). In addition, it has been shown that nanoparticles together with transition metals induce ROS production which exhibits a synergistic effect of nanoparticles together with transition metals (36).…”
Section: Cytotoxicity and Oxidative Stressmentioning
confidence: 99%